2008
DOI: 10.1002/biot.200700065
|View full text |Cite
|
Sign up to set email alerts
|

Diseases of protein aggregation and the hunt for potential pharmacological agents

Abstract: Protein aggregation is a ubiquitous phenomenon significant to all aspects of science. Notably, the formation of protein aggregates is frequently encountered in biochemical research and biopharmaceutical industry. Formation of protein aggregates is generally regarded to be associated with partially folded intermediate species that are susceptible to self-association due to the exposure of hydrophobic core. Evidence supports the concept that the formation of aggregates in vitro is a generic property of proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 342 publications
(415 reference statements)
0
16
0
Order By: Relevance
“…The exposed hydrophobicity can lead to protein insolubility and the formation of intracellular aggregates (1). Aggregate formation and the long term cellular persistence of aggregates are thought to be the underlying causes of many devastating human pathologies including Alzheimer, Parkinson, Huntington, and amyotrophic lateral sclerosis (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The exposed hydrophobicity can lead to protein insolubility and the formation of intracellular aggregates (1). Aggregate formation and the long term cellular persistence of aggregates are thought to be the underlying causes of many devastating human pathologies including Alzheimer, Parkinson, Huntington, and amyotrophic lateral sclerosis (2).…”
mentioning
confidence: 99%
“…One central means is the elimination of misfolded proteins via protein quality control (PQC) 2 degradation. Eukaryotic PQC degradation is generally mediated by ubiquitin-protein ligases that ubiquitinate misfolded proteins for subsequent proteasome degradation (3).…”
mentioning
confidence: 99%
“…As misfolded proteins accumulate and overwhelm the primary PQC systems, they can progressively oligomerize and aggregate in the cell [151]. It is now well understood that the etiology for dozens of degenerative human diseases is linked to the oligomerization and aggregation of misfolded proteins [2, 151]. These diseases are typically characterized by the age-dependent accumulation of pathogenic misfolded proteins into visible cellular inclusions [2, 151].…”
Section: Nuclear Pqc – Inclusion Sitesmentioning
confidence: 99%
“…It has been revealed that misfolded protein aggregation underlies the pathology for many devastating human disorders such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis (ALS), and prion disorders like Creutzfeldt-Jakob [2]. Presently, it is not clear how misfolding and aggregation cause cellular toxicity in each pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular mechanism for cataract formation could be useful for designing alternative treatment or for designing drugs that may delay the onset of the process. Most investigations concerning the causes of cataracts focus on the changes in lens proteins (crystallins) [7,8] since cataract is a disease of protein aggregation [9]; however, since protein stability is maintained by protein-protein, protein-lipid, and other such interactions, alterations in lipid composition of lens could also be a contributing or predisposing factor for development of cataract.…”
Section: Introductionmentioning
confidence: 99%